2011
DOI: 10.1002/jcp.22639
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bone morphogenetic protein‐2 and osteoactivin for mesenchymal cell differentiation: Effects of bolus and continuous administration

Abstract: Current osteoinductive protein therapy utilizes bolus administration of large doses of bone morphogenetic proteins (BMPs), which is costly, and may not replicate normal bone healing. The limited in vivo biologic activity of BMPs requires the investigation of growth factors that may enhance this activity. In this study, we utilized the C3H10T1/2 murine mesenchymal stem cell line to test the hypotheses that osteoactivin (OA) has comparable osteoinductive effects to bone morphogenetic protein-2 (BMP-2), and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 64 publications
1
16
1
Order By: Relevance
“…The present results confirm these findings and moreover demonstrate that lowfrequency mechanical stimulation can enhance osteogenic differentiation of C2C12 cells in the presence of BMP-2. BMP-2 alone induces expression of bone marker genes such as alkaline phosphatase (Alp), Osteopontin, and collagen type I [25], and we have clearly shown here that concomitant low-frequency mechanical stimulation has a synergistic effect on C2C12 osteogenic differentiation depending on the timing of these costimuli. These findings are consistent with those of previous studies involving significantly different mechanical conditions, notably higher oscillatory stimulation frequencies [26][27][28].…”
Section: Discussionmentioning
confidence: 66%
“…The present results confirm these findings and moreover demonstrate that lowfrequency mechanical stimulation can enhance osteogenic differentiation of C2C12 cells in the presence of BMP-2. BMP-2 alone induces expression of bone marker genes such as alkaline phosphatase (Alp), Osteopontin, and collagen type I [25], and we have clearly shown here that concomitant low-frequency mechanical stimulation has a synergistic effect on C2C12 osteogenic differentiation depending on the timing of these costimuli. These findings are consistent with those of previous studies involving significantly different mechanical conditions, notably higher oscillatory stimulation frequencies [26][27][28].…”
Section: Discussionmentioning
confidence: 66%
“…Since the necessity for high dosage amounts of BMP2 to achieve bone healing [15][16][17] is one of the major challenges faced in clinical research, this observation is particularly significant. The scaffold though has superior mechanical properties as compared to other injectable gel-based biomaterials, might not be enough to match the mechanical properties of in vivo bone.…”
Section: Discussionmentioning
confidence: 98%
“…To ensure that there is enough BMP2 remaining at the treatment site to have any therapeutic effect, BMP2 dosage of more than 100-fold of physiological concentration has to be introduced in the bone scaffolds. However, higher than natural BMP2 dosage (around 5 μg) leads to undesirable cytotoxic and inflammatory effects, increased osteoclastic activity (bone resorption), uncontrolled ectopic bone formation, and carcinoma [15][16][17]. Based on in vitro and in vivo studies, a low dose of BMP2 with a sustained release profile has been found optimal for osteogenesis [18][19][20].…”
Section: Introductionmentioning
confidence: 98%
“…On other hands, previous studies showed that GPNMB, NDRG1, and IGF1R were cell differentiation markers (29)(30)(31). GPNMB (Glycoprotein NMB, Osteoactivin) was reported to be an essential protein during the differentiation of osteoblast (32). N-Myc downstream-regulated gene 1 (NDRG1), also named differentiation-related gene-1, is involved in the development of central nervous system (33).…”
Section: Discussionmentioning
confidence: 99%